EPG characteristics of velar stops in normal adult English speakers - Liker, Marko (Array, 2007)
This study aimed to determine the main characteristics of normal tongue palate patterns for velar stops. EPG data from the EUR-ACCOR database were analysed for nonsense VCV sequences containing /k/ in nine vowel contexts for seven English speaking adults. Incomplete EPG closure across the palate for /k/ occurred in 19% (range 4%-41%) of utterances with the most number of incomplete closures in /aka/ and the least in /uki/. As predicted, place of articulation was dependant on vowel context. The most fronted was the velar occlusion in /iki/ and the most retracted in /aka/. In terms of amount of contact, /k/ in /iki/ environment had almost twice as much tongue palate contact compared to /aka/ in all speakers (mean 42% for /iki/ compared to 22% for /aka/). There was considerable interspeaker variability in all variables. The implications of the results for diagnosing and treating speech disorders are discussed.